DNA Methylation Array Identifies Golli-MBP as a Biomarker for Disease Severity in Childhood Atopic Dermatitis - Chen, Kuang-Den; Huang, Ying-Hsien; Guo, Mindy Ming-Huey; Chang, Ling-Sai; Chu, Chi-Hsiang; Bu, Li-Feng; Chu, Chiao-Lun; Lee, Chih-Hung; Liu, Shih-Feng; Kuo, Ho-Chang (Journal of investigative dermatology, 2022)
In this study, we investigated the changes in global methylation status and its functional relevance in childhood atopic dermatitis (AD). Differences in epigenome-scale methylation events in peripheral blood associated with childhood AD were screened using DNA methylation arrays of 24 patients with AD compared with 24 control subjects. Of the 16,840 differentially methylated CpG regions between AD and control subjects, >97% CpG loci revealed hypomethylation in patients with childhood AD. Among the globally hypomethylated loci, we identified two CpG clusters within the golli-mbp locus of the MBP gene, which was functionally enriched by subnetwork enrichment analysis as an orchestrator among associated genes. The differential hypomethylation of the top-ranked cg24700313 cluster in the golli-mbp locus was validated by pyrosequencing in an independent cohort of 224 children with AD and 44 control subjects. DNA methylation was found to be negatively correlated with disease severity but showed no significant correlation with IgE levels after age adjustment. The multivariate correlation analysis represents a higher score in AD intensity with significantly increased IgE levels and decreased methylation levels in cg27400313. We concluded that methylation loss in the golli-mbp locus is an epigenetic factor associated with disease severity of childhood AD.